FILSAFAT ILMU SEBAGAI LANDASAN PENELITIAN SOSIAL - Dessy Dwisusila; Muhammad Zaim; Harris Effendi Thahar (Jurnal Education and Development, 2023)
The philosophical study of social research is an important dimension of social science that has been positioned to analyze the problem description of social science and its relationships. This research describes social phenomena in the natural sciences and deals with the intellectual influence of various aspects of social science knowledge on the social world. Social research boils down to debating legitimate studies through a philosophical approach. The method used is content and qualitative analysis. Secondary data is taken and collected from various print sources such as newspapers, publications, books, articles. The results can be concluded that the philosophy of science is treated as a fundamental basis of social scientific research that analyzes research techniques from an analytical point of view of the truth and reality of the social world. Philosophy of social science deals with the general meaning of things and is centered on shared experiences about the social world in which people's perspectives differ from one another. Social science has always been multiperspective and multicultural which facilitates in making various claims about the best way to understand the social world